The impact of fixed exchange rates on fiscal discipline - Makram El-Shagi (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2009)
In this paper, it is shown that, contrary to standard arguments, fiscal discipline is not substantially enhanced by a fixed exchange rate regime. This study is based on data from 116 countries collected from 1975 to 2004 and uses various estimation techniques for dynamic panel data, in particular a GMM estimation in the tradition of Arellano and Bover (1995), and Blundell and Bond (1998). Contrary to previous papers on this topic, the present paper takes into account that the consequences of a new exchange rate regime do not necessarily fully manifest immediately.
Keywords: F31; E63; O23; 330